Helmuth Plessner's Social and Political Thought in Light of his Philosophy of Life (Diametros, 2020)
The essay contains an analysis of selected socio-political ideas of Helmuth Plessner. The basic assumption of this study is the existence of a close categorial relationship between Plessner’s reflections in The Limits of Community (1924) and in Die Stufen des Organischen (1928). As the interpretative key, the author uses one of the pivotal concepts of Plessner’s philosophy of life, namely the category of “border.” Showing the adequacy of this category in relation to Plessner’s social and political concepts, the essay addresses the issue of the individual-society relationship, the question of social roles and their possible deviations, and the problem of political leadership.